2011
DOI: 10.1080/10408398.2010.482217
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Fruit and Vegetable Intake in Human Intervention Studies: A Systematic Review

Abstract: Observational evidence consistently shows that consumption of a diet rich in fruit and vegetables may offer protection against diseases such as cardiovascular disease and cancer. Assessment of dietary intake is complex and prone to many sources of error. More objective biomarkers of fruit and vegetable intake are therefore of interest. The aim of this review is to examine the usefulness of the main biomarkers of fruit and vegetable intake to act as objective indicators of compliance in dietary intervention stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 133 publications
2
89
0
Order By: Relevance
“…A 12-week period was chosen for this study as this has been shown to be sufficient time to ensure an increase in micronutrient status [11] in response to FV interventions, and also to induce changes in plasma C-reactive protein (CRP) and urinary isoprostanes [12,13]. Interleukin (IL)-8 has recently been shown to be responsive to 10-week dietary interventions (with bread [14] and cheese [15]).…”
Section: Methodsmentioning
confidence: 99%
“…A 12-week period was chosen for this study as this has been shown to be sufficient time to ensure an increase in micronutrient status [11] in response to FV interventions, and also to induce changes in plasma C-reactive protein (CRP) and urinary isoprostanes [12,13]. Interleukin (IL)-8 has recently been shown to be responsive to 10-week dietary interventions (with bread [14] and cheese [15]).…”
Section: Methodsmentioning
confidence: 99%
“…However, because flexible sigmoidoscopy-which only assesses the distal (left-sided) colon and rectum-was used for screening, proximal adenoma could not be evaluated, and the results observed for distal or rectal adenoma may not be generalizable to proximal adenoma. Dietary assessment is also complex and FFQs are not a perfect measure of habitual dietary intakes; therefore, intakes of some foods, including fruit and vegetables, may have been underestimated because of difficulty in the accurate recall of usual intakes (32). Whereas the misreporting and misclassification was likely equal between groups, it may still have reduced the ability to detect associations and resulted in residual confounding.…”
Section: Tablementioning
confidence: 99%
“…; lutein, zeaxanthin, ÎČ-cryptoxanthin, lycopene, α-carotene and ÎČ-carotene) were used as biomarkers of fruit and vegetable intake [17,18]. The plasma concentrations were determined with high-performance liquid chromatography (HPLC).…”
Section: Carotenoidsmentioning
confidence: 99%
“…Although the available recovery or prediction biomarkers do not capture total intake of these food groups on an absolute scale, it is possible to distinguish between high and low intakes of these food groups using concentration biomarkers. Plasma carotenoids are considered to reflect the intake of fruits and vegetables in a satisfactory manner [17,18] and are amongst the most commonly used concentration biomarkers in dietary validation studies today. In a "western diet", approximately 80 to 90 % of the total carotenoid intake derives from fruit and vegetable consumption of which yellow-orange fruits and vegetables and dark green leafy vegetables are particularly rich in carotenoids [17].…”
Section: Introductionmentioning
confidence: 99%